2020
DOI: 10.3390/molecules25143279
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Attributes of Cantharidin: Involved Molecular Mechanisms and Pathways

Abstract: Cancer is a preeminent threat to the human race, causing millions of deaths each year on the Earth. Traditionally, natural compounds are deemed promising agents for cancer treatment. Cantharidin (CTD)—a terpenoid isolated from blister beetles—has been used extensively in traditional Chinese medicines for healing various maladies and cancer. CTD has been proven to be protein phosphatase 2A (PP2A) and heat shock transcription factor 1 (HSF-1) inhibitor, which can be potential targets for its anticancer activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 90 publications
0
34
0
Order By: Relevance
“…The use of cantharidin as an aphrodisiac is known all over the world [ 43 ] and it also functions as a diuretic, and for the treatment of warts; again it comes with a warning that the consumption can be fatal [ 44 ]. Modern medicine has shown that cantharidin extracted from male blister beetles can be used as a medicine, e.g., it can suppress liver, pancreatic, colon, bladder and breast cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of cantharidin as an aphrodisiac is known all over the world [ 43 ] and it also functions as a diuretic, and for the treatment of warts; again it comes with a warning that the consumption can be fatal [ 44 ]. Modern medicine has shown that cantharidin extracted from male blister beetles can be used as a medicine, e.g., it can suppress liver, pancreatic, colon, bladder and breast cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic dose is close to the toxic dose, with a lethal oral dose of 10‐60 mg and a median lethal dose (LD 50 ) of 1.71 mg/kg in mice 5 . CTD can cause damage to multiple organs, including the liver, kidney, myocardium, bladder and small intestine, with liver injury being particularly serious 6,7 . Cantharidin induces the production of d‐reactive oxygen species (ROS) and an increase in lipid peroxidation, resulting in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cantharidin can inhibit the proliferation of leukemic cells, induce apoptosis, block the cell cycle, and enhance the inhibitory effect of chemotherapeutic drugs [9][10][11]. In addition, it can delay tumor progression, invasion, and metastasis [12]. At present, the therapeutic mechanism employed by mylabris against tumors remains unknown.…”
Section: Introductionmentioning
confidence: 99%